2004
DOI: 10.1076/iceh.52.1.47.23922
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic Susceptibility: Multidimensional Relationships With Cloninger?s Tridimensional Personality Questionnaire, COMT Polymorphisms, Absorption, and Attentional Characteristics

Abstract: One hundred and seven healthy volunteers were administered Cloninger's Tridimensional Personality Questionnaire (TPQ), the Differential Attentional Processes Inventory (DAPI), the Tellegen Absorption Scale (TAS), and the Stanford Hypnotic Susceptibility Scale, Form C (SHSS:C). Polymorphisms of catechol O-methyltransferase (COMT), an enzyme involved in dopamine metabolism, were assessed. Highly hypnotizable subjects self-reported greater TPQ persistence, absorption, and focused attentional abilities. Hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 92 publications
3
55
0
2
Order By: Relevance
“…Just like one of our earlier studies (Szekely et al, 2010), several other investigations described the association between hypnotizability and COMT, the dopamine-degrading enzyme (catechol-O-methyltransferase) (see Lichtenberg, Bachner-Melman, Ebstein, and Crawford (2004);Lichtenberg, Bachner-Melman, Gritsenko, and Ebstein (2000); Raz (2005) ;Raz, Fan, and Posner, (2006)). …”
Section: Hypnosis and The Oxytocin Systemmentioning
confidence: 93%
“…Just like one of our earlier studies (Szekely et al, 2010), several other investigations described the association between hypnotizability and COMT, the dopamine-degrading enzyme (catechol-O-methyltransferase) (see Lichtenberg, Bachner-Melman, Ebstein, and Crawford (2004);Lichtenberg, Bachner-Melman, Gritsenko, and Ebstein (2000); Raz (2005) ;Raz, Fan, and Posner, (2006)). …”
Section: Hypnosis and The Oxytocin Systemmentioning
confidence: 93%
“…Based on the pivotal role ascribed to the prefrontal executive control network for absorbed attention and positive symptoms in schizophrenia, it was further hypothesized that Absorption is associated with the COMT val158met polymorphism affecting the dopaminergic neurotransmitter system. (Interestingly, we have observed association between hypnotizability and the COMT gene 169,170 .) In the Ott et al study, 167 the group with the T/T genotype of the HTR2A T102C polymorphism had significantly higher Absorption scores while no main effect was found for the COMT polymorphism.…”
mentioning
confidence: 99%
“…Strong evidence emerged from existing studies that the polymorphisms in DRD4, DRD2 and 5-HTTLPR were not connected to novelty-seeking personality (Burt, McGue, Iacono, Comings, & MacMurray, 2002;de Brettes et al, 1998;Ebstein, 2006;Ebstein et al, 1997;Hill, Zezza, Wipprecht, Locke, & Neiswanger, 1999;Kluger, Siegfried, & Ebstein, 2002;Kreek, Nielsen, Butelman, & LaForge, 2005; S. H. Lee, Ham, Cho, Lee, & Shim, 2007;Light et al, 2007;Munafò et al, 2003;Ricketts et al, 1998;Samochowiec et al, 2001;Schinka, Letsch, & Crawford, 2002;Suzuki et al, 2008;Tsuchimine et al, 2012;Van Gestel et al, 2002). In contrast, studies on COMT polymorphism revealed mixed and conflicting results (Calati et al, 2011;Demetrovics et al, 2010;Golimbet, Alfimova, Gritsenko, & Ebstein, 2007;Hashimoto et al, 2007;Hosák, Libiger, Cizek, Beránek, & Cermáková, 2006;Hoth et al, 2006;Kim, Kim, Kim, Lee, & Kim, 2006;Lichtenberg, Bachner-Melman, Ebstein, & Crawford, 2004;Light et al, 2007;Reuter & Hennig, 2005; S.-J. Tsai, Hong, Yu, & Chen, 2004).…”
Section: Novelty-seekingmentioning
confidence: 99%
“…Individuals with greater harm-avoidance or lesser risk-taking personality tend to be cautious, fearful, nervous, discouraged, doubtful, inhibited, and shy in most social situations (Kose, 2003). Studies on the DRD4, DRD2 and COMT polymorphisms revealed mixed and conflicting results (Bau, Roman, Almeida, & Hutz, 1999;Dreber et al, 2009;Enoch, Xu, Ferro, Harris, & Goldman, 2003;Golimbet et al, 2007;Hashimoto et al, 2007;Hill et al, 1999;Kim et al, 2006;Kuhnen & Chiao, 2009;Lichtenberg et al, 2004;Light et al, 2007;Munafò et al, 2003;Smolka et al, 2005;Tsai et al, 2004;Tsuchimine et al, 2012). Meta-analyses and review studies indicated that there was no connection between 5-HTTLPR polymorphism and harm-avoidance personality (Ebstein, 2006;Munafò et al, 2009;Schinka, Busch, & RobichauxKeene, 2004;Sen, Burmeister, & Ghosh, 2004).…”
Section: Harm-avoidancementioning
confidence: 99%